EKSISTENSI OTONOMI DESA PAKRAMAN DALAM PERSPEKTIF PLURALISME HUKUM - Atu Dewi, Anak Agung Istri Ari (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 3 (2014)DO - 10.24843/JMHU.2014.v03.i03.p13, 2014)
The purpose of this research is to discover the existence of autonomy of Desa Pakraman in legal pluralism perspective. Related with that purpose, there are two issues that will be discussed, first, how does the existence of the autonomy of Desa Pakraman in Indonesia’s legal system?,Second, how does the existence of the autonomy of Desa Pakraman in legal pluralism perspective?. The research method is normative legal research using statue approach, concept approach and analytical approach and law analysis by using legal interpretation. Based on the problems, the results of discussion are : first, the existence of the autonomy of Desa Pakraman within the Indonesia’s legal system has regulated in the 1945 Constitution of the Republic of Indonesia, national and local Regulations. In the Constitution, specifically Article 18 B of paragraph (2), declare that the states recognizes Desa Pakraman and their traditional rights. In regulation of Law No.5 of 1960 concerning basic Agrarian Law (UUPA), regulation of Human Rights, and regulation of Desa (Village) are clearly recognize Desa Pakraman as traditional institution has traditional rights, one of it is the autonomy of Desa Pakraman. At the local regulation, autonomy Desa Pakraman has regulated in Local Regulation about Desa Pakraman. Second, that existence of autonomy Desa Pakraman in perspective legal pluralism is that the existence autonomy Desa Pakraman is a weak legal pluralism. In perspective weak legal pluralism the state law as a superior and the customary law as an inferior, its position in the hierarchy under State law. As a theory, the semi-autonomous social field from Sally Falk Moore perspectives that Desa Pakraman is semi-autonomous. Desa Pakraman has capacity to hold their village based on the customary law and outomaticly Desa Pakraman to be in framework of state law.
Keywords: Existence, autonomy, Desa Pakraman, legal pluralism, Indonesia’s legal system